Macronutrient and mineral contents of five local black rice (Oryza sativa) cultivars in Indonesia (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Nashrurrokhman M, Sayekti PR, Safitri A, Purwestri YA, Pratiwi R. 2019. Macronutrient and mineral contents of five local black rice (Oryza sativa) cultivars in Indonesia. Biodiversitas 20: 3647-3653. Nutrient composition is important information that can be used to support the development of black rice as functional food. In this study, the macronutrient and mineral compositions of five black rice cultivars were determined by measuring the contents of total carbohydrates, proteins, and lipids, and levels of the minerals Ca, Fe, and Zn of whole rice, refined rice, and rice bran. Rice samples were obtained from farmers who planted the black rice cultivars of Woja Laka, Toraja, Cempo Ireng “Seyegan”, Melik “Bantul” and Wedomartani. Proximate analysis and spectrophotometric methods were performed to measure the contents of macronutrients and minerals. Statistical analysis of all quantitative data was conducted by using One-way analysis of variance (ANOVA) (p
Keywords: Black rice, functional food, macronutrient, micronutrient